OVAJRIAN HYPER STIMULATION IN ASSISTED REPRODUCTION (SRI LANKAN EXPERIENCE - Kaluarachchi, A; Senevirathne, H R; Wijeyaratne, S; Nelson, C; Gunawardana, V (My University, 2012)
With the development of new techniques of assisted reproduction in the treatment of infertility ovarian hyperstimulation syndrome is a potentially serious complication which is encountered more frequently. This is a new problem seen in Sri Lanka with the introduction of assisted teproduction. We report four cases of ovarian hyperstimulation syndrome during assisted reproduction at one of the centres in Sri Lanka